2017
DOI: 10.18203/2320-6012.ijrms20170649
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of knowledge and practices regarding breast feeding amongst mothers belonging to tribal community in Melghat area, Amravati, Maharashtra, India

Abstract: Background: Delayed breastfeeding initiation, colostrum deprivation, supplementary feeding of breast milk substitutes, early introduction of complementary feeding, and incorrect weaning from breast milk are commonly found practices in tribal communities around the world. Aim of the study was to assess the breast-feeding knowledge and practices among mothers belonging to tribal community and having children less than 1 years of age in Melghat area, Maharashtra, India.Methods: Present cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is much higher than the findings of Khan et al where it was 35% and Chavan et al where it was 36.45%. 13,9 This may be due to difference in cultural beliefs among the mothers in these studies as they were conducted in Karnataka and Maharashtra respectively. The 'Continued Breastfeeding at 1-year' indicator was 100%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is much higher than the findings of Khan et al where it was 35% and Chavan et al where it was 36.45%. 13,9 This may be due to difference in cultural beliefs among the mothers in these studies as they were conducted in Karnataka and Maharashtra respectively. The 'Continued Breastfeeding at 1-year' indicator was 100%.…”
Section: Discussionmentioning
confidence: 95%
“…5,3 Similar findings were reported by different authors wherein the value ranged from 81% to 88%. [6][7][8][9][10] This may be explained by the inclusion of tribal or backward class populations in these studies. It was much higher in studies conducted by Nisha et al where it was 98.6% and Madhu et al where it was 97%.…”
Section: Discussionmentioning
confidence: 98%
“…This is a significant omission; acute malnutrition is very prevalent with high rates of death and morbidity that need specific treatment and preventive measures [10]. Maternal low knowledge, negative attitudes, low self-efficacy, and cultural influences and taboos all have a significant impact on mothers' infant-feeding practices and their children's eating patterns [11]. Studies conducted in different parts of the world, such as in Brazil, revealed that knowledge, culture, self-efficacy, and beliefs are strong predictors of IYCFP [12].…”
Section: Introductionmentioning
confidence: 99%
“…Every day, between 3000 and 4000 infants die in poor countries as a result of diarrhea and severe respiratory infections caused by a lack of breast milk. In Ghana, only around 12.0% of young children are fed with infant feeding bottles [9,10]. While undernutrition (low weight for age) is widely recognized, the relevance of acute malnutrition is rarely, if ever, emphasized.…”
Section: Introductionmentioning
confidence: 99%